Entrepreneurship as networking : mechanisms, dynamics, practices, and strategies - Elfring, Tom, 1957-; Klyver, Kim; Burg, Elco van, 1983- (Oxford University Press, 2021)
"In this book we present entrepreneurship as networking as a perspective. Persistent problems around the dominant 'individual-opportunity' approach in the entrepreneurship field motivated us to focus on the social-interactive aspects and action orientation of entrepreneurship. It promises to address the challenge of providing a more integrated account in which the entrepreneur's agency is combined with a greater emphasis on the social environment. The importance of social relations and the associated interactions between entrepreneurs and their environment give insight into key entrepreneurial processes. We address the guiding questions of what a viable network is for (nascent) entrepreneurs and how networking activities affect their entrepreneurial endeavours. Therefore, we first create a synthesis of key network mechanisms and networking dynamics. This allows us to (a) shed new light on the origins of opportunities and improve our understanding of how entrepreneurs access resources and subsequently mobilize and deploy them and (b) explain how entrepreneurs build legitimacy, facilitating them to act on perceived new combinations and thereby exploit their potential. Thus, we highlight how networking is a central constitutive force in entrepreneurship. Previous work showed how networks can or will lead to entrepreneurial action as a facilitator. Going one step further, we posit that networking is entrepreneurial action, and entrepreneurial action is networking, thereby opening an entirely new research agenda"